2016
DOI: 10.1039/c6ra03902b
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation kinetics and cluster structure of amino-PEG covered gold nanoparticles

Abstract: In this study controlled clustering kinetics is demonstrated for PEG grafted gold nanoparticles, in response to applied environmental stimuli; the temperature and ionic strength of the medium. It is also found that the rate of assembly determines the structure of the prepared clusters. After the system is brought out of equilibrium, time-dependent extinction and dynamic light scattering data are used to follow the evolution of nanoparticle cluster formation in real time. The results show that the rate of assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In our previous article [25], we showed that the analytical solution of a non-lumped kinetic model is still possible despite the fact that it has an infinite number of concentration variables. The model itself was based on pervious experimental results and theoretical considerations [4,5,[26][27][28][29][30][31]. In the present work, we show that similar analytical solutions can be found in a limited number of other kinetic models as well.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…In our previous article [25], we showed that the analytical solution of a non-lumped kinetic model is still possible despite the fact that it has an infinite number of concentration variables. The model itself was based on pervious experimental results and theoretical considerations [4,5,[26][27][28][29][30][31]. In the present work, we show that similar analytical solutions can be found in a limited number of other kinetic models as well.…”
Section: Introductionsupporting
confidence: 72%
“…A general nucleation-growth type kinetic model In this paper, a general class of models for nanoparticle formation will be considered, which is based on previous attempts to build such models and a comparison of experimental results [4,5,[26][27][28][29][30][31]. The model contains three different kinds of steps, two of which represent nucleation, whereas the third one includes particle growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, novel nanoparticle‐based superstructures should combine the properties of the building blocks and the emerging new features that can be achieved solely based on the self‐assembly of the nanocrystals. This challenging task has called numerous assembly procedures into being: triggering the responsive ligand shell, [ 11,12 ] cross‐linking, [ 13,14 ] ligand desorption, [ 15 ] solvent exchange, [ 16 ] controlled solvent evaporation, [ 17 ] applying templates, [ 18 ] or using the cryoaerogelation method. [ 19,20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Both understanding and having control of these interactions can help to rationally design higher order structural elements. [6][7][8] Most studies investigate the assembly of nanoscopic building blocks into structures and patterns at the nanoscale or the assembly of nanoparticles and colloids into microstructures (e.g., nanocrystals). 9-18 Solvent evaporation induced self-assembly techniques are also commonly used to prepare assemblies at desired solid substrates with macroscopic dimensions.…”
Section: Introductionmentioning
confidence: 99%